2018
DOI: 10.1177/0011128718772100
|View full text |Cite
|
Sign up to set email alerts
|

Judicial Trustworthiness in Africa: Do Macro-Level Conditions Matter?

Abstract: The current study’s primary goal was to assess the extent to which specific macro-level conditions cause variation in citizens’ levels of trust in courts across 33 African countries. Using an advanced analytical technique, results revealed that a country’s levels of democracy has a significant and positive relationship with citizens’ trust in the court. However, institutional corruption and crime (homicide rate) had significant and negative relationship with citizens’ trust in the court. Moreover, findings obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…Looking first at sociodemographic characteristics, we can see that women and younger respondents tend to lend greater trust to the judicial system, replicating the results of previous studies (Bühlmann and Kunz, 2011; Roussey and Deffains, 2012; Salzman and Ramsey, 2013; Aydın Çakır and Şekercioğlu, 2016; Garoupa and Magalhães, 2020). Furthermore, like Aydın Çakır and Şekercioğlu (2016) and Boateng and Ajorlolo (2019)—but contrary to Salzman and Ramsey (2013)—we also find that trust seems to increase with respondents’ education.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…Looking first at sociodemographic characteristics, we can see that women and younger respondents tend to lend greater trust to the judicial system, replicating the results of previous studies (Bühlmann and Kunz, 2011; Roussey and Deffains, 2012; Salzman and Ramsey, 2013; Aydın Çakır and Şekercioğlu, 2016; Garoupa and Magalhães, 2020). Furthermore, like Aydın Çakır and Şekercioğlu (2016) and Boateng and Ajorlolo (2019)—but contrary to Salzman and Ramsey (2013)—we also find that trust seems to increase with respondents’ education.…”
Section: Resultscontrasting
confidence: 54%
“…Hansen shows that higher crime rates are associated with lower trust in courts in parliamentary constituencies in the United Kingdom (2017:1514). Boateng and Adjorjolo's (2019) study of Afrobarometer data shows that in African countries with higher homicide rates, trust in the judicial system tends to be lower. Another way to indirectly capture the relationship between judicial performance and trust is to focus on the amount of resources poured into the judicial system.…”
Section: The Correlates Of Trust In the Legal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not well studied, the amount of freedom that citizens and the media enjoy has been observed to predict trusting relationship with an institution. For example, using an advance analysis to examine factors that influence people’s attitudes toward the police and courts in Africa, Boateng and colleagues (Boateng & Adjorlolo, 2018; Boateng & Buckner, 2017) argued that citizens living in countries where the press enjoys tremendous amount of freedom tend to view the institutions to be legitimate and trustworthy. Past research has also found a positive relationship between happiness and confidence in institutions such as the police (Cao & Dai, 2006; Cao & Stack, 2005).…”
Section: Trust and Confidence In Criminal Justicementioning
confidence: 99%
“…2012 in Ghana, 2017 in Kenya; 2020 in Malawi) and the potential to plunge the countries into chaos. African courts in several instances have also provided guidance on electoral reforms.12 Yet, it is imperative to emphasise that the contributions of the courts to the health of democracies are not "uniformly and evenly distributed across the continent" (Boateng andAdjorlolo 2019, 1691). While countries like Ghana, Kenya and South Africa have performed significantly well when it comes to dispute resolution through the formal court system, others like the Central African Republic, Liberia, and South Sudan lag behind following many years of civil wars that have affected the development of formal legal systems in these countries (Boateng and Adjorlolo 2019).…”
Section: The Judiciarymentioning
confidence: 99%